1997
DOI: 10.1093/toxsci/39.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response for the Stimulation of Cell Division by Caffeic Acid in Forestomach and Kidney of the Male F344 Rat

Abstract: Caffeic acid (CA, 3,, at 2% in the diet, had been shown to be carcinogenic in forestomach and kidney of F344 rats and B6C3F1 mice. Based on its occurrence in coffee and numerous foods and using a linear interpolation for cancer incidence between dose 0 and 2%, the cancer risk in humans would be considerable. In both target organs, tumor formation was preceded by hyperplasia, which could represent the main mechanism of carcinogenic action. The dose-response relationship for this effect was investigated in male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…These U-shaped dose-response relationships in two critical target organs display enhanced cellular division at the higher doses. Lutz et al (85) suggested that the low-dose response of a delayed cell division may account to some extent for the cancer-protective effect seen in previous bioassays as noted above.…”
Section: Effects Of Caffeic Acid On the Stimulation Of Cell Division mentioning
confidence: 94%
See 1 more Smart Citation
“…These U-shaped dose-response relationships in two critical target organs display enhanced cellular division at the higher doses. Lutz et al (85) suggested that the low-dose response of a delayed cell division may account to some extent for the cancer-protective effect seen in previous bioassays as noted above.…”
Section: Effects Of Caffeic Acid On the Stimulation Of Cell Division mentioning
confidence: 94%
“…(=) This hypothesis was subsequently evaluated by Lutz et aZ. (85) in which male F344 rats were fed caffeic acid at five different dietary concentrations including the controls (i.e., 0, 0.05, 0.14, 0.40, and 1.64 percent) for 4 weeks. The total number of epithelial cells per unit comparison in the forestomach was increased nearly 2.5-fold at the two highest concentrations, whereas no treatment effects were observed at 0.05 percent, the lowest dose studied.…”
Section: Effects Of Caffeic Acid On the Stimulation Of Cell Division mentioning
confidence: 99%
“…Caffeic acid is recognized to have potential effect in scavenging reactive species of oxygen and nitrogen [6]. However, there is no report on the effect of this chemical on tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, MGMT has been hypothesized to be responsible for hormetic dose-responses following exposure to alkylating agents [44,45]. As MGMT is an inducible enzyme and repairs the highly mutagenic O 6 -methylguanine lesion, induction of MGMT would readily explain the reduction in mutant frequency observed by Thomas et al It is acknowledged that there may be additional underlying mechanisms for hormesis, which include but are not limited to alterations in apoptosis [46,47], [48], [49], [50] cell proliferation [42,51,52] and antioxidant capacity [53] , [54,55], [56], [57], [25] .…”
Section: P53 Status May Contribute To the J-shaped Dose-responsementioning
confidence: 99%